2008
DOI: 10.1118/1.2955746
|View full text |Cite
|
Sign up to set email alerts
|

The use of new GAFCHROMIC® EBT film for I125 seed dosimetry in Solid Water® phantom

Abstract: Radiochromic film dosimetry has been extensively used for intravascular brachytherapy applications for near field within 1 cm from the sources. With the recent introduction of new model of radiochromic films, GAFCHROMIC EBT, with higher sensitivity than earlier models, it is promising to extend the distances out to 5 cm for low dose rate (LDR) source dosimetry. In this study, the use of new model GAFCHROMIC EBT film for 125I seed dosimetry in Solid Water was evaluated for radial distances from 0.06 cm out to 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 42 publications
1
57
0
Order By: Relevance
“…An estimate of the combined uncertainties has been calculated using a simple quadrature sum of individual components to provide an overall uncertainty. The detailed step‐by‐step analysis of the uncertainties of the measured doses is described by Chiu‐Tsao et al (1) According to MC simulations, the values obtained for type A uncertainty were less than 0.1% for all points except for the longitudinal axis (z‐axis) points where the statistical uncertainty was below 0.5%. The statistical uncertainty in the simulation of air‐kerma strength is less than 0.4%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An estimate of the combined uncertainties has been calculated using a simple quadrature sum of individual components to provide an overall uncertainty. The detailed step‐by‐step analysis of the uncertainties of the measured doses is described by Chiu‐Tsao et al (1) According to MC simulations, the values obtained for type A uncertainty were less than 0.1% for all points except for the longitudinal axis (z‐axis) points where the statistical uncertainty was below 0.5%. The statistical uncertainty in the simulation of air‐kerma strength is less than 0.4%.…”
Section: Discussionmentioning
confidence: 99%
“…Radiochromic film is a powerful 2D dosimeter, which exhibits useful characteristics including high spatial resolution, near tissue/water equivalence false(normalZeff,EBT=6.98,normalZeff,water=7.3false), 1 , 2 the possibility of using in water, and lower sensitivity to visible light. In addition, it has been shown to have an energy independence response for HDR brachytherapy applications 3 , 4 …”
Section: Introductionmentioning
confidence: 99%
“…Another method to fit a curve to the delivered dose (D) versus measured netOD is using an analytical expression: ( 27 , 28 , 20 ) Dfit=b.netOD+citalicnetODn where b , c and n are the fitting parameters. Since Devic et al ( 20 ) found that the fit procedure returns the best results for a fitting parameter of normaln=2.5, other two parameters were calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Air kerma strength (S K ) for GZP6 HDR brachytherapy system from Monte Carlo code was obtained 4414 × 10 −6 and 4077 × 10 −6 Gy m 2 h −1 for source of CH 3 and CH 4 , respectively. The value of measured air kerma strength was obtained by taking into account the date of measurement 4207 × 10 −6 ± 1% Gym 2 h −1 for CH 3 and 3864.5 × 10 −6 ± 1% Gym 2 h −1 for CH 4 .…”
Section: Gzp6 Hdr Brachytherapymentioning
confidence: 99%
“…3 Different investigators had demonstrated the usefulness of the EBT Gafchromic films for brachytherapy source dosimetry. 4 These films require no chemical processing and they are insensitive to ambient light. Therefore, they can be cut to the shape of the experimental geometry for the best representation of a dosimetric setup.…”
Section: Introductionmentioning
confidence: 99%